Heterogeneous origami-architected materials with variable stiffness - Yasuhiro Miyazawa (Nature Portfolio, 2021)
Origami-inspired metamaterials are attractive for their programmable shape-shifting properties but are typically characterized by low structural rigidity. Here, 3D heterogeneous origami structures display highly reconfigurable mechanical properties, including finely controllable and reversible stiffness variation.